Technology-Driven Marketing Development: Evidence from Artificial Intelligence, Big Data, Augmented Reality, and Internet of Things - Sarah Balqis Binti Sabarudin; Sanjeta A/P Jeeva; Sanjeev Singh A/L Avtar Singh; Sahel Fawwaz Muhammad Syareef; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Technological advancement has become a central driver of contemporary marketing development, influencing how firms engage customers, build brand loyalty, and sustain competitive advantage. This study examines the impact of Artificial Intelligence (AI), Augmented Reality (AR), Big Data, and the Internet of Things (IoT) on marketing development, using Apple Inc. as the empirical context. A quantitative research design was employed, with data collected through a structured survey questionnaire from 152 respondents. Multiple regression analysis was conducted using SPSS to test the proposed relationships. The results indicate that the model explains 68.3% of the variance in marketing development (R² = 0.683). Big Data shows the strongest influence on marketing development (? = 0.376), followed by AI (? = 0.301) and IoT (? = 0.219), while AR demonstrates a positive but comparatively weaker effect (? = 0.069). Overall, the findings confirm that technology-driven initiatives play a significant role in enhancing marketing development and supporting sustained competitiveness in the digital era. This study contributes empirical evidence by comparing the relative influence of key emerging technologies within a single organizational context and offers practical insight for firms seeking to align technological adoption with effective marketing development strategies.